Bioinspired Nitroalkylation for Selective Protein Modification and Peptide Stapling. (16th January 2020) - Mahesh, Sriram; Adebomi, Victor; Muneeswaran, Zilma P.; Raj, Monika
Abstract: Nitroalkanes react specifically with aldehydes, providing rapid, stable, and chemoselective protein bioconjugation. These nitroalkylated proteins mimic key post‐translational modifications (PTMs) of proteins and can be used to understand the role of these PTMs in cellular processes. Demonstrated here is the substrate scope of this bioconjugation by attaching a variety of tags, such as NMR tags, fluorescent tags, affinity tags, and alkyne tags, to proteins. The structure and enzymatic activity of modified proteins remain conserved after labeling. Notably, the nitroalkane group leads to easy characterization of proteins by mass spectrometry because of its distinct fingerprint pattern. Importantly, the nitro‐alkylated peptides provide a new handle for site‐selective fluorination of peptides, thus installing a specific probe to study peptide–protein interactions by 19 F NMR spectroscopy. Furthermore, nitroalkane reagents can be used for the late‐stage diversification of peptides and for the synthesis of peptide staples. Abstract : Ausgezeichnet : Eine bioinspirierte Nitroalkylierungsstrategie ermöglicht die chemoselektive Modifikation von Proteinen, die eine wichtige posttranslationale Modifikation (PTM) nachahmt. Verschiedene Tags wurden schnell und mit hohen Umsätzen (99 %) unter milden Reaktionsbedingungen an Proteinen installiert. Die Nitro‐Peptid‐Konjugate bieten einen Ansatzpunkt für die positionsselektive Fluorierung von Peptiden.